2018
DOI: 10.1097/olq.0000000000000742
|View full text |Cite
|
Sign up to set email alerts
|

Early Evidence of the Effectiveness of the Human Papillomavirus Vaccination Program Against Anogenital Warts in Manitoba, Canada: A Registry Cohort Study

Abstract: Women vaccinated at an older (≥19 years) age may be less protected against AGWs, particularly if sexually active before vaccine administration. Further efforts should be targeted at increasing vaccine uptake among preadolescents before the initiation of sexual activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…26 Clinical markers suggestive of prior sexual activity were determined using a composite measure of pregnancy, STIs, Pap testing, or contraceptive drug use. 25 Any female with evidence of any of these outcomes prior to the index date was considered "sexually active" for the purpose of this study. Information on STIs was obtained from the provinicial Communicable Disease Surveillance Database.…”
Section: Other Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Clinical markers suggestive of prior sexual activity were determined using a composite measure of pregnancy, STIs, Pap testing, or contraceptive drug use. 25 Any female with evidence of any of these outcomes prior to the index date was considered "sexually active" for the purpose of this study. Information on STIs was obtained from the provinicial Communicable Disease Surveillance Database.…”
Section: Other Covariatesmentioning
confidence: 99%
“…3 In 2013, vaccine uptake in this age group was slightly lower (65%) in Manitoba than the national average (73%). 9 Another publicly funded program targeted at [19][20][21][22][23][24][25][26] old women at higher risk of HPV infection was initiated in November 2012, and lasted for 2 years. 10 Eligibility for the "high-risk" catch-up program was at the discretion of the care provider, but the program's literature emphasized vaccinating women with a history of early onset sexual activity, multiple sex partners, adolescent pregnancy, immune-compromising illness, previous STIs or abnormal cervical cytology or family history of HPV-associated cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluations were in countries that used 2vHPV (seven), 4vHPV (27) or both (one). Nine studies evaluated effectiveness for prevention of prevalent (detected at a single time point) or incident vaccine-type (4vHPV or 2vHPV) HPV infection [11,12,[25][26][27][28][29][30][31], ten anogenital warts [13][14][15][16][17][18][32][33][34][35], and 16 cervical cytological or histological abnormalities [19][20][21][22][23][24][36][37][38][39][40][41][42][43][44][45].…”
Section: Search Resultsmentioning
confidence: 99%
“…Estimates of vaccine effectiveness in the US were also comparable to that observed in other counties; a provincial cohort study in Canada found a 56% vaccine effectiveness against anogenital warts among those who received three doses before the age of 18. 26 Similarly, an effectiveness study set in Sweden found a 76% vaccine effectiveness for those who received three doses before the age of 20. 27…”
Section: Discussionmentioning
confidence: 98%